Combined Experimental and Theoretical Study of Weak Polyelectrolyte Brushes in Salt Mixtures - Willott, Joshua D (Langmuir : the ACS journal of surfaces and colloids, 2019)
The swelling behavior of a hydrophobic poly(2diisopropylamino)ethyl methacrylate (PDPA) brush immersed in aqueous solutions of single and mixed salts has been investigated using ellipsometry and numerical self-consistent field (nSCF) theory. As a function of solution ionic strength, the osmotic and salted brush regimes of weak polyelectrolyte brushes as well as substantial specific anion effects in the presence of K+ salts of Cl-, NO3-, and SCN- are found. For solutions containing mixtures of NO3- and Cl-, the brush swelling is the same as one would expect on the basis of the concentration-weighted average of the brush behavior in the single salt solutions. However, in mixtures of SCN- and Cl-, the swelling response is more complicated and substantial divergence from ideal behavior is observed. Mean-field theory shows excellent qualitative agreement with the ellipsometry findings. nSCF reveals that for the SCN-/Cl- cases the swelling behavior of the PDPA brush most likely arises from the predominant localization of the weakly hydrated SCN- within the brush compared to the more strongly hydrated Cl-